Is there a place for a multidisciplinary “Heart Team” approach to the selection of myocardial revascularization method in patients with acute coronary syndromes? - O. L. Barbarash; V. I. Ganyukov; R. S. Tarasov; L. S. Barbarash (Российский кардиологический журнал)
Current review article, based on foreign and Russian studies, guidelines of the European and North American cardiological and surgical communities, summarizes the expert positions on the place of multidisciplinary “Heart Team” approach in the selection of management strategy for patients with various types of coronary artery disease. The positions of modern clinical guidelines regarding percutaneous coronary intervention and coronary artery bypass grafting in acute coronary syndrome are given. Prospective positions for optimizing the decisionmaking process by a multidisciplinary team when considering difficult patients are presented.